Evidence for higher-than-average air temperatures after the 8.2 ka event provided by a Central European δ18O record. (15th September 2017) - Andersen, Nils; Lauterbach, Stefan; Erlenkeuser, Helmut; Danielopol, Dan L.; Namiotko, Tadeusz; Hüls, Matthias; Belmecheri, Soumaya; Dulski, Peter; Nantke, Carla; Meyer, Hanno; Chapligin, Bernhard; von Grafenstein, Ulrich; et al.
Abstract: The so-called 8.2 ka event represents one of the most prominent cold climate anomalies during the Holocene warm period. Accordingly, several studies have addressed its trigger mechanisms, absolute dating and regional characteristics so far. However, knowledge about subsequent climate recovery is still limited although this might be essential for the understanding of rapid climatic changes. Here we present a new sub-decadally resolved and precisely dated oxygen isotope (δ 18 O) record for the interval between 7.7 and 8.7 ka BP (10 3 calendar years before AD 1950), derived from the calcareous valves of benthic ostracods preserved in the varved lake sediments of pre-Alpine Mondsee (Austria). Besides a clear reflection of the 8.2 ka event, showing a good agreement in timing, duration and magnitude with other regional stable isotope records, the high-resolution Mondsee lake sediment record provides evidence for a 75-year-long interval of higher-than-average δ 18 O values directly after the 8.2 ka event, possibly reflecting increased air temperatures in Central Europe. This observation is consistent with evidence from other proxy records in the North Atlantic realm, thus most probably reflecting a hemispheric-scale climate signal rather than a local phenomenon. As a possible trigger we suggest an enhanced resumption of the Atlantic meridional overturning circulation (AMOC), supporting assumptions from climate model simulations. Highlights: A new high-resolution lake sediment δ 18 Oostracods from Europe record is presented. It covers the interval 7.7–8.7 ka BP and reflects changes in δ 18 Oprecip . The 8.2 ka event is reflected by a ∼1.1‰ drop in δ 18 O at 8231–8080 varve years BP. A so far not documented δ 18 O overshoot (∼0.4‰) occurs at 8080–8005 varve years BP. This interpreted as pronounced warming triggered by an enhanced AMOC resumption.